Consistency between Gleason score of prostate biopsy and radical prostatectomy: predictors of increased tumour grading - O. Yu. Nesterova; M. G. Varentsov; N. A. Oleynikova; A. A. Strigunov; I. A. Zhestkov; D. A. Okhobotov; D. M. Kamalov; N. I. Sorokin; A. A. Kamalov (Вестник урологии, 2024)
Introduction. Gleason grading is one of the key parameters for determining the prostate cancer (risk group after receiving the results of a prostate biopsy in addition to the level of prostate-specific antigen (PSA). However, an important clinical issue arises from changes in this grading following radical surgery. In some cases, such discrepancies in data can lead to a shift in patient management tactics from radical surgery to active follow-up recommended for patients with low cancer risk.Objective. To assess the consistency of the results of prostate biopsy and radical prostatectomy with an assessment of possible predictors of increased tumor Gleason grading.Materials & methods. Between 2019 and 2021, 193 patients with prostate cancer were selected for treatment at the Medical Centre of Moscow State University. Of these, 139 patients were chosen for the final analysis of Gleason tumour grading consistency after biopsy and radical prostatectomy.Results. The results of prostate biopsy and radical prostatectomy were comparable in 54.7% of patients (n = 76), while the remaining 45.3% (n = 63) showed a change in Gleason gradaing after radical prostatectomy: 29.5% (n = 41) patients showed an increased gradation, and 15.8% (n = 22) — decrease. Most often, the data were consistent for patients with a Gleason score 7: 63.6% for 3 + 4 = 7 and 57.9% for 4 + 3 = 7. The highest percentage of graduation increase was observed for patients from the group 3 + 3 = 6 and amounted to 48%. Cohen's kappa value was 0.351 (p < 0.001), indicating poor consistency between the results of the two studies. The total number of biopsies was associated with an increase in Gleason score after radical prostatectomy (OR = 0.816; 95% CI = 0.680 – 0.978). For example, the odds of Gleason tumour grading decreases by 18.4% when the number of biopsy specimens per unit increasesConclusion. The concordance of Gleason grading of prostate cancer after prostate biopsy and radical prostatectomy remains poor. The only predictor of improved concordance is the biopsy count, thereby reflecting biopsy quality and encouraging clinicians to move away from sextant biopsies to systematic and targeted biopsies. Increasing the consistency of results can provide more accurate staging and classification of patients according to cancer risk, thereby influencing future management.